2022
DOI: 10.3389/fenvs.2022.942263
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Three Types of Soils on Biogas Slurry Ammonium Nitrogen

Abstract: Using farmland to digest biogas slurry is an effective measure to overcome the bottleneck of sewage treatment in livestock and poultry farms. However, there is limited research on the soil adsorption characteristics of biogas slurry ammonium nitrogen (NH4+-N). In addition, the maximum adsorption capacity (Qm) of farm soil is unclear. In this study, three typical farmland tillage layer soils (silty loam, loam, and sandy loam) were used to analyze adsorption characteristics through adsorption kinetics experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is different from the traditional approaches such as seed soaking, foliar fertilizer, base fertilizer, top dressing fertilizer, hydroponics and animal feed [ 39 , 40 , 41 ]. To ensure the environmental safety of this approach, the soil maximum adsorption on biogas slurry ammonium nitrogen was researched [ 42 ], and the aging characteristics and fate analysis of biogas slurry ammonium nitrogen disposal in soil were also researched by simulation experiments [ 43 ] before this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is different from the traditional approaches such as seed soaking, foliar fertilizer, base fertilizer, top dressing fertilizer, hydroponics and animal feed [ 39 , 40 , 41 ]. To ensure the environmental safety of this approach, the soil maximum adsorption on biogas slurry ammonium nitrogen was researched [ 42 ], and the aging characteristics and fate analysis of biogas slurry ammonium nitrogen disposal in soil were also researched by simulation experiments [ 43 ] before this study.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, on the two transient charge soils, the effects of phosphate on glyphosate adsorption were more important than on the permanent charge soil. Previous studies revealed significantly enhancement in crop growth and yield due to application of phosphorus in glyphosate contaminated soils Wang et al [15]. As phosphate and glyphosate were applied to the soils in various orders, the adsorption concentrations of glyphosate…”
Section: Annals Of Reviews and Researchmentioning
confidence: 99%
“…on the soils varied, as follows: GPS-soil > GPS-P-soil = GPS-soil-P > P-soil-GPS, implying that glyphosate, phosphate, and the soils had a complex relationship Wang et al [15]. Using these products raises the plant's biomass while reducing the harmful effects of toxins in the environment.…”
Section: Annals Of Reviews and Researchmentioning
confidence: 99%
“…As a small molecule with three polar functional groups (carboxyl, amino, and phosphonate), glyphosate is strongly sorbed by soil minerals after application [7,9,23,[28][29][30][31] and has a half-life of 3-174 days in soil minerals and 5-91 days in water [32]. Even though the carboxylic group can also contribute to glyphosate sorption in soil, it usually occurs through the phosphonic acid group (organic compounds that contain C-PO(OH) 2 or C-PO(OR) 2 ) [3,7,28,33,34]. Considering soil glyphosate contact time variations and soil phosphate accumulation, three different glyphosate applications were applied.…”
Section: The Application Of Glyphosatementioning
confidence: 99%